2008
DOI: 10.1111/j.1365-2036.2008.03788.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the pharmacogenetics of azathioprine in the treatment of inflammatory bowel disease

Abstract: SUMMARY BackgroundOne-third of patients with inflammatory bowel disease (IBD) receiving azathioprine (AZA) withdraw treatment due to side effects or lack of clinical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 56 publications
5
139
2
3
Order By: Relevance
“…On the contrary, several studies in Western samples have addressed the impact of TPMT activity and genotype on the clinical response of IBD patients treated with AZA/6-MP and suggested that measurement of TPMT activity might predict clinical response to AZA/6-MP. 15,16 At present, the reasons for discrepancies among these studies are unclear. However, one possible explanation for these discrepancies is that the Asian population has genetic backgrounds of TPMT that are different from those of the Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, several studies in Western samples have addressed the impact of TPMT activity and genotype on the clinical response of IBD patients treated with AZA/6-MP and suggested that measurement of TPMT activity might predict clinical response to AZA/6-MP. 15,16 At present, the reasons for discrepancies among these studies are unclear. However, one possible explanation for these discrepancies is that the Asian population has genetic backgrounds of TPMT that are different from those of the Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…40 Genetic alterations in the ITPase gene, and thus a decreased ITPase activity, are associated with adverse outcomes of conventional thiopurine therapy, probably by the accumulation of 6-thioinosine-triphosphate (6TITP). 41,42 Since 6TITP is a substrate for TPMT, accumulation of 6TITP may result in accumulation of 6-MMPR (Fig. 1).…”
Section: 29mentioning
confidence: 99%
“…A recent prospective British study in IBD patients (n ¼ 207) found that similar to TPMT deficiency, ITPA deficiency (both determined by genotyping) was also a predictor of AZA adverse effects. 34 Notably, this study also reported that carrying a heterozygous TPMT genotype strongly predicted adverse effects (79% heterozygous vs 35% wild-type TPMT, Po0.001). These observations suggest that taking into considerations the benefits for carriers of heterozygous TPMT alleles may substantially improve the overall cost-effectiveness of TPMT genotyping for patients prescribed AZA.…”
Section: Methodsmentioning
confidence: 73%